Acute Onset of Exogenous Endophthalmitis after Dexamethasone Implant Injection Treated without Implant Removal. (18th November 2018) - Bastakis, George G.; Stavrakakis, Anastasios; Nikolaos, Avgoustinakis; Dimopoulos, Dimitris; Pappas, George
Abstract : We present a case of acute endophthalmitis after intravitreal dexamethasone implant injection and discuss the management of this rare and challenging case in which the implant could not be removed. A 50-year-old woman with a history of branch retinal vein occlusion in the right eye was treated with intravitreal dexamethasone implant injection for macular oedema. Four days after injection, the patient was admitted to the department with acute pain, decreased vision, and redness. A diagnosis of acute post-intravitreal injection endophthalmitis was made. A 23-guage (23G) vitrectomy was performed immediately to remove the implant, and a vitreous tap for culture and polymerase chain reaction was acquired during the procedure. We were unable to remove the dexamethasone implant during the vitrectomy because of dense membrane formation. At the end of the procedure, we injected intravitreal antibiotics (vancomycin and amikacin), and the patient was treated with fortified topical antibiotics and steroids. At the time of writing, 5 years later, the patient retains a best corrected visual acuity of 10/10 (6/6) with dexamethasone implant therapy maintenance. Intravitreal dexamethasone implant-associated endophthalmitis is a rare and challenging condition. Immediate 23G pars plana vitrectomy, even without removal of the implant, can lead to favourable visual results.